Transport behaviors of plastic particles in saturated quartz sand without and with biochar/Fe3O4-biochar amendment - Tong, M.; He, L.; Rong, H.; M. Li; Kim, H. (Water Research, 2020)
As an environmentally friendly material, biochar has been widely used to remediate soil/water contaminants such as heavy metals and organic pollutants. The addition of biochar or modified biochar to porous media might affect the retention of plastic particles and thus influence their fate in natural environment. In this study, both biochar and magnetic biochar (Fe3O4-biochar) were synthesized via a facile precipitation method at room temperature. To determine the significance of biochar and Fe3O4-biochar amendment on the transport and deposition behaviors of plastic particles, the breakthrough curves and retained profiles of three different sized plastic particles (0.02 μm nano-plastic particles, and 0.2 μm and 2 μm micro-plastic particles) in quartz sand were compared with those obtained in quartz sand either with biochar or Fe3O4-biochar amendment in both 5 mM and 25 mM NaCl solutions. The results show that for all three different sized plastic particles under both examined solution conditions, the addition of biochar and Fe3O4-biochar in quartz sand decreases the transport and increases the retention of plastic particles in porous media. Fe3O4-biochar more effectively inhibits the transport of plastic particles than biochar. We found that the addition of biochar/Fe3O4-biochar could change the suspension property and increase the adsorption capacity of porous media (due to the increase of porous media surface roughness and negatively decrease the zeta potentials of porous media), contributing to the enhanced deposition of plastic particles. Moreover, we found that negligible amount of biochar and Fe3O4-biochar (<1%) were released from the columns following the plastic particle transport when the columns were eluted with very low ionic strength solution at high flow rate (to simulate a sudden rainstorm). Similarly, small amount of plastic particles were detached from the porous media under this extreme condition (16.5% for quartz sand, 14.6% for quartz sand with biochar amendment, and 7.5% for quartz sand with Fe3O4-biochar amendment). We found that over 74% of the Fe3O4-biochar can be recovered from the porous media after the retention of plastic particles by using a magnet and 87% plastic particles could be desorbed from Fe3O4-biochar by dispersing the Fe3O4-biochar into 10 mM NaOH solution. In addition, we found that the amendment of unsaturated porous media with biochar/Fe3O4-biochar also decreased the transport of plastic particles. When biochar/Fe3O4-biochar were added into porous media as one layer of permeable barrier near to column inlet, the decreased transport of plastic particles could be also obtained. The results of this study indicate that magnetic biochar can be potentially applied to immobilize plastic particles in terrestrial ecosystems such as in soil or groundwater. © 2019 Elsevier Ltd
Keywords: Adsorption; Adsorption capacities; article; atmospheric transport; Bio chars; biochar; charcoal; chemical bond; controlled study; crystal structure; Deposition; ecosystem; Fourier transform infrared spectroscopy; Groundwater; heavy metals; immobilization; Ionic strength; iron oxide; Iron oxides; Magnetic biochar; magnetic method; magnetic separation; Magnetism; magnetite; magnetite nanoparticle; organic pollutant; Organic pollutants; Particle size; pH; plastic; Plastic particle; Plastic particles; plastic waste; Plastics; pollutant transport; porosity; Porous materials; Porous media; porous medium; Precipitation (chemical); Precipitation methods; priority journal; Quartz; Retention; Sand; silicon dioxide; Sodium chloride; Sodium hydroxide; soil amendment; Storms; surface area; surface property; Surface roughness; suspension; Suspension properties; Suspensions (fluids); Synthesis; terrestrial ecosystems; Unsaturated polymers; Unsaturated porous media; X ray photoemission spectroscopy; zeta potential